Security of Sustainable Development in the Post-Pandemic Crisis on the Basis of an Inclusive Circular Economy - Pavlikha, Natalia; Shuliak, Antonina; Skorokhod, Iryna; Tsymbaliuk, Iryna; Voichuk, Maksym (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/014, 2021)
The study involves the formation of a modern paradigm of sustainable development security in a post-pandemic crisis period, based on an inclusive circular economy. The research is aimed to address the fundamental problem of strengthening the sustainable development security to overcome the effects of the post-pandemic crisis at the micro, meso, and macro levels on the basis of the sustainable, ecological, carbon-neutral economy, in the context of the importance and interdependence of each component in the process of the socio-ecological-economic rise of society. The results of the study will be the development of the theoretical and methodological basis of an inclusive circular economy, scientific and practical justification of approaches to overcoming the effects of the post-pandemic crisis by developing a mechanism to strengthen sustainable development security, and recommendations for possible threats to state food security in the post-pandemic period. The goal of this scientific research is theoretical and methodological substantiation of the formation of an inclusive circular economy and forecasting the capacity of the organic market in Ukraine for economic growth, social justice, environmental management.